Association of Obesity with Obstructive Sleep Apnea - Monowarul Abedin Khan; D G M Akaiduzzaman; Md Zaforullah Chowdhury (Update Dental College, 2023)
Background: Obstructive sleep apnea (OSA) is a global disease with a rising incidence along with its co-morbidities, especially the metabolic syndrome. One of the main components contributing to sleep apnea is obesity. Objective: To evaluate the association of obesity with obstructive sleep apnea (OSA). Method: This cross-sectional analytical study was conducted in the Department of Otolaryngology, Sir Salimullah Medical College Hospital, Dhaka, and in Bangladesh ENT Hospital, Dhaka, from March 2019 to February 2020. One hundred patients with OSA were enrolled in this study. After taking the written consent, the clinical history, as well as the findings of the physical examination of each patient were recorded. Quantitative data were expressed as mean and standard deviation, and qualitative data were expressed as frequency and percentage. Statistical analysis was performed using SPSS-20. Ap-value <0.05 was considered statistically significant. Results: The mean age of the study subjects was 45.25±8.81 years within a range of 18-60 years. Males (73.0%) were predominant than female (27.0%). The male to female ratio was 2.7:1. The frequency of obesity was 89.0% among OSA patients. Most of the study subjects had severe OSA (69.0%) followed by moderate (22.0%) and mild (9.0%) in this study. The severity of OSA was significantly higher among obese patients. Apnoea-hypopnea index was significantly higher in obese (49.09±23.34) than non-obese patients (19.70±8.92).75.3% of obese patients had severe OSA, 19.1% had moderate OSA and 5.6% had mild OSA. There was a significant positive correlation of BMI with Apnoca-hypopnea index(r=0.84 and p=0.009). Conclusion: Obesity has an association with the obstructive sleep apnea (OSA). Update Dent. Coll. j: 2023; 13(1): 27-30